The Mind-Brain Problem as a False Problem - Quaresma, Alexandre (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
Orthodox cognitivism sees biology and bioevolution as phenomena that are totally despicable and irrelevant in relation to the mechanism and functionalist determinism that it uses as a premise and logical tool to try to understand biological reality. Our aim in this article is to draw attention to the fact that there is no reliable evidence to support this kind of mechanistic view. How could the part be equivalent to the whole, the content to the continent, a residue of the operation vital to the operation itself? In short, the mind-brain problem that cognitivism creates for itself —as we intend to demonstrate— is actually a false problem.